2014
DOI: 10.1111/cts.12137
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Elevated Levels of C‐Reactive Protein on Circulating Endothelial Progenitor Cell Function

Abstract: In vitro, C-reactive protein (CRP) impairs endothelial progenitor cell (EPC) function; however, the influence of CRP on EPCs in vivo is unclear. We determined whether EPC function is impaired in adults with elevated plasma CRP concentrations, independent of other risk factors. EPCs were harvested from 75 adults (43 males, 32 females): 25 with low CRP (< 1.0 mg/L); 25 with moderate CRP (1.0–3.0 mg/L); and 25 with high CRP (> 3.0 mg/L). The capacity of EPCs to form colonies (colony assay), migrate (Boyden chambe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…CRP is a protein produced by the liver as a response to acute inflammation and regulated in response to interleukin‐6 (IL‐6) or interleukin‐1β (IL‐1β) in hepatocytes [25]. Recent reports have revealed that an increased CRP level as part of the inflammatory response leads to endothelial dysfunction by reducing endothelial nitric oxide synthase and downregulating angiogenesis and has an inverse correlation with the functions of endothelial progenitor cells that participate in vascularization and secretion of angiogenic growth factors [26, 27]. Jun JH reported that CRP might regulate abnormal vessel formation in liver cirrhosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…CRP is a protein produced by the liver as a response to acute inflammation and regulated in response to interleukin‐6 (IL‐6) or interleukin‐1β (IL‐1β) in hepatocytes [25]. Recent reports have revealed that an increased CRP level as part of the inflammatory response leads to endothelial dysfunction by reducing endothelial nitric oxide synthase and downregulating angiogenesis and has an inverse correlation with the functions of endothelial progenitor cells that participate in vascularization and secretion of angiogenic growth factors [26, 27]. Jun JH reported that CRP might regulate abnormal vessel formation in liver cirrhosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that increased CRP levels as part of the inflammatory response lead to endothelial dysfunction by reducing endothelial nitric oxide synthase and down-regulating angiogenesis as well as by an inverse correlation with functions of endothelial progenitor cells that participate in vascularization and secrete angiogenic growth factors [ 17 , 18 ]. Also, Enjoji et al reported that CRP and VEGF showed a positive correlation in acute cholangitis patients, but in chronic PBC patients, the correlation was not significant [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the culprit was shown to be the increase in mitochondrial ROS generation that was aggravated by CRP effect in modulating the expression of the anti-oxidant enzymes glutathione peroxidase and Mn superoxide dismutase (MnSOD) [76]. However, recent work by Fasing et al showed no association between CRP plasma level and circulating EPCs [77].…”
Section: C-reactive Protein (Crp)mentioning
confidence: 99%